Extracranial Facial Nerve Schwannoma—Histological Surprise or Therapeutic Planning? - Daniela Vrinceanu; Mihai Dumitru; Matei Popa-Cherecheanu; Andreea Nicoleta Marinescu; Oana-Maria Patrascu; Florin Bobirca (Medicina, 2023)
Schwannomas (neurilemomas) are benign, slow-growing, encapsulated, white, yellow, or pink tumors originating in Schwann cells in the sheaths of cranial nerves or myelinated peripheral nerves. Facial nerve schwannomas (FNS) can form anywhere along the course of the nerve, from the pontocerebellar angle to the terminal branches of the facial nerve. In this article, we propose a review of the specialized literature regarding the diagnostic and therapeutic management of schwannomas of the extracranial segment of the facial nerve, also presenting our experience in this type of rare neurogenic tumor. The clinical exam reveals pretragial swelling or retromandibular swelling, the extrinsic compression of the lateral oropharyngeal wall like a parapharyngeal tumor. The function of the facial nerve is generally preserved due to the eccentric growth of the tumor pushing on the nerve fibers, and the incidence of peripheral facial paralysis in FNSs is described in 20–27% of cases. Magnetic Resonance Imaging (MRI) examination is the gold standard and describes a mass with iso signal to muscle on T1 and hyper signal to muscle on T2 and a characteristic “darts sign.” The most practical differential diagnoses are pleomorphic adenoma of the parotid gland and glossopharyngeal schwannoma. The surgical approach to FNSs requires an experienced surgeon, and radical ablation by extracapsular dissection with preservation of the facial nerve is the gold standard for the cure. The patient’s informed consent is important regarding the diagnosis of schwannoma and the possibility of facial nerve resection with reconstruction. Frozen section intraoperative examination is necessary to rule out malignancy or when sectioning of the facial nerve fibers is necessary. Alternative therapeutic strategies are imaging monitoring or stereotactic radiosurgery. The main factors which are considered during the management are the extension of the tumor, the presence or not of facial palsy, the experience of the surgeon, and the patient’s options.